Experiment with weather - Bower, Miranda (Minneapolis, Minn. : Lerner Publications Co., 1994)
Provides an introduction to meteorological phenomena and includes experiments describing various aspects of our weather, such as clouds, wind, fog, and rainbows.
Includes index.
Booklist.
Horn Book.
School Library Journal.
4.5.
4.5
Keywords: Meteorology -- Juvenile literature; Weather -- Juvenile literature; Weather -- Experiments -- Juvenile literature; Experiments; Meteorology; Weather -- Experiments; Meteorology; Weather -- Experiments